2010
DOI: 10.1108/19852511011055943
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary disclosure by Shariah approved companies: an exploratory study

Abstract: Purpose -The purpose of this paper is to investigate the extent of voluntary disclosure (EVD) (i.e. overall, conventional, and Islamic disclosure) in the annual reports of Shariah Approved Companies (ShAC) listed on Bursa Malaysia. Design/methodology/approach -A disclosure index was developed, which consists of 59 items (including items related to the Shariah, i.e. Islamic items), to measure the EVD in the annual reports of ShAC. Secondary data from annual reports were analyzed using descriptive statistics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
3
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(105 citation statements)
references
References 13 publications
7
90
3
5
Order By: Relevance
“…By considering all items are equally important this study used unweighted approach to score the items in disclosure index 1989;Hossain et.al., 1994;Wallace et al, 1994;Naser et.al. 2002;Ousama and Fatima;2010) Analyzing the presence or absence of particular items of information is a most commonly used from of content analysis (Patten, 2002). Therefore, this study also analyze the present or absent of 83 disclosure items which are shown in Table 1 and the companies were awarded one (1) if the item is present and zero (0) if the item is absent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By considering all items are equally important this study used unweighted approach to score the items in disclosure index 1989;Hossain et.al., 1994;Wallace et al, 1994;Naser et.al. 2002;Ousama and Fatima;2010) Analyzing the presence or absence of particular items of information is a most commonly used from of content analysis (Patten, 2002). Therefore, this study also analyze the present or absent of 83 disclosure items which are shown in Table 1 and the companies were awarded one (1) if the item is present and zero (0) if the item is absent.…”
Section: Methodsmentioning
confidence: 99%
“…Studies such as Naser et.al 2002;Barako et al 2006;Ousama and Fatima;2010;Al-Shammari, 2013 identified the level of voluntary disclosures and Studies such as Cerf 1961;cooke 1992;Ahmed and Nicholls 1994;Wallace et.al.1994;Meek et.al. 1995;Inchausti, 1997;Naser et.al.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In addition the research on the ISR is also expected to provide some benefits: firstly, for the company, it can take into consideration to disclose CSR that contain religious values (ISR) which is adequate and in accordance with Islamic principles. As a corporate citizen, SCC has obligation to be engaged in charitable activities and treat justly for all stakeholders as taught in Islam (Ousama and Fatima 2010). Secondly, for investors, they can do special considerations to assess the extent to which the performance of company is in accordance with sharia.…”
Section: Introductionmentioning
confidence: 99%
“…profitability) was commonly used to examine the influence of voluntary disclosure (i.e. Ousama and Fatima 2010;Istianingsih 2015). Therefore, three variables of company characteristics such as profitability, company size, and type of industry that have been tested in previous studies are included as independent variables in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The pace of development in the Islamic capital market has created the formation of various international Islamic organisations to study and promote this alternative market and has brought up Malaysia as an international Islamic finance hub (Nazri et al, 2014). Today, the Islamic capital market runs parallel to the conventional capital market and provide investors an alternative investment philosophy that is rapidly gaining acceptance and entrance by Muslims and non-Muslims (Ousama & Fatima, 2010b). …”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%